Lioness rampant - Pierce, Tamora (New York : Random House, 1997)
Alanna continues to create her own life as a female warrior when she and new companions journey to the Roof of the World seeking the powerful Dominion Jewel, perhaps the last hope of saving her country from dissension and hostile magic.
"Originally published in hardcover by Atheneum, a division of Macmillan Publishing Company, in 1988. Published by arrangement with Atheneum Books for Young Readers, Simon & Schuster Children's Publishing Division"--T.p. verso.
Reading level: 6.3.
Age level: 10 and up.
Keywords: Alanna, -- of Trebond -- (Fictitious character) -- Fiction; Knights and knighthood -- Fiction; Middle Ages -- Fiction; Sex role -- Fiction; Fantasy fiction; Young adult fiction